Urgensi Pendidikan Seks di Sekolah: Mencegah Bukan Mengajarkan - Virna Fathia; Zakiyatunnavis Bransah; Zuliana Zuliana (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
One of the most important preventive efforts to protect children from sexual violence is sex education. The implementation of sex education is sometimes delayed or ignored because many people still misunderstand it as a method of education about sexual behavior. The purpose of this study is to highlight the importance of providing sex education to children so that they can protect themselves from potential sexual exploitation. The approach used is a literature review of several books, scientific journals, and related policy documents. Based on the results of the study, children who do not receive sex education are more likely to experience violence, engage in inappropriate sexual behavior, and be exposed to misinformation from the media or their environment. It has been proven that appropriate sex education that is in accordance with the child's developmental stage helps children become more self-aware, understand their own body's limitations, and gain the ability to say "no" and ask for help. The conclusion of this study highlights that sex education is a form of early childhood education that involves the responsibility of parents, teachers, society, and government and does not explicitly teach sexual activity. The implications of this study indicate that integrated sex education from an early age can be a national strategy in preventing sexual violence against children.